2019
DOI: 10.1007/s00348-019-2789-z
|View full text |Cite
|
Sign up to set email alerts
|

Particle image velocimetry measurements of a thermally convective supercritical fluid

Abstract: Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…(i) The characteristic velocity becomes asymmetric, as found in previous numerical [13,16,17] and experimental studies [25,26], and (ii) the shape of the velocity and temperature profiles inside the boundary layers changes due to temperature-dependent fluid properties.…”
Section: A Derivationmentioning
confidence: 56%
See 3 more Smart Citations
“…(i) The characteristic velocity becomes asymmetric, as found in previous numerical [13,16,17] and experimental studies [25,26], and (ii) the shape of the velocity and temperature profiles inside the boundary layers changes due to temperature-dependent fluid properties.…”
Section: A Derivationmentioning
confidence: 56%
“…This is nontrivial and has so far not been done experimentally because Pr m andX are both intrinsic properties of a fluid. Previous experiments and simulations have been conducted at fixed T m with varyingX by changing and P m , thus causing also changes in Ra m and Pr m [11,14,17,19,25,26]. Manipulating the degree of the NOB effect in such a way always results also in a change of Ra m , which also changes the heat flux.…”
Section: Experimental Program and The Description Of The Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors' knowledge, no experimental studies about direct velocity measurements in high speed non-ideal flows were found in the literature up to date. A recent research (Valori et al 2019) applied PIV to an unconventional vapor in highly non-ideal state. However, the analyzed conditions were low temperature and high pressure, and the study dealt with natural convection, thus the flow field featured extremely low velocity.…”
Section: Introductionmentioning
confidence: 99%